Public relations crisis communication : a new model - Anderson-Meli, Lisa; Koshy, Swapna (New York : Routledge, Taylor & Francis Group, 2021)
"This book explores the definition, nature and context of public relations crises; it also examines and defines the main elements of public relations crises and positions it in the context of the current communication sphere. Public Relations Crisis Communication: A New Model investigates existing group communication theories, including organizational culture, critical theory of organizations, media ecology, public rhetoric, and cross-cultural communication theory to establish the relevance in the context of the new model of public relations crisis. Key concepts from existing public relations crisis theory are also discussed and validated in order to establish prevailing thought. Through a case study of Malaysia Airlines MH370, involving a textual analyses of press communications on the Malaysia Airlines website, this book scrutinises prevailing theory and definitions. Most valuably, this book proposes a new definition and model of public relations crisis, alongside a suggested extension to existing crisis communication theory. This will help to improve the ability to address divergent publics with differing priorities in public relations crisis communication. This book is of interest to students, teachers, researchers and practitioners of Public Relations, Communication, Media and Marketing, professionals in the aviation industry and those in international relations"--
Includes bibliographical references and index.
Keywords: Public relations; Corporate culture; Communication